Development of Immunopathobiogenesis on SIRS-Sepsis - A Guntur Hermawan (The Indonesian Biomedical Journal, 2009)
Over the past decade, sepsis has been diagnosed according to consensus guidelines established in 1991 as an infection in addition to the symptoms of systemic inflammatory response syndrome (SIRS). In addition to the previous criteria, the 2001 conference added several new diagnostic criteria for sepsis. Of particular interest was the inclusion of the biomarkers procalcitonin (PCT) and C-reactive protein (CRP), despite the overall conclusion that it was premature to use biomarkers for sepsis diagnosis. The primary recommendation of the panel was the implementation of the Predisposition, insult Infection, Response, and Organ dysfunction (PIRO).The immune system has traditionally been devided into innate and adaptive components, each of which has a different role and function in defending the host against infectious agents. Stimulation of different TLRs induces distinct patterns of gene expression, which not only leads to the activation of innate immunity but also increasing evidence supports an additional critical role for TLRs in orchestrating the development of adaptive immune responses.The superantigens are able to induce toxic shock syndrome and can sometimes cause multiple organ failure via adaptive immune system. The superantigenic activity of the bacterial exotoxins can be attributed to their ability to cross-link major histocompatibility complex class II molecules on antigen-presenting cells outside the peptide groove with T-cell receptors to form a trimolecular complex. This trimolecular interaction leads to uncontrolled release of a number of proinflammatory cytokines. Proinflammatory cytokines especially IFN-γ and TNF-α, the key cytokines causing toxic shock syndrome.KEYWORDS: sepsis, innate immunity, adaptive